National Security, Boko Haram Insurgency and the International Dimensions of Terrorism - Afinotan, (PhD), L. A; Olaleye, (PhD), Adedayo O.; Afinotan, V.E.C. (Covenant University Journal of Politics and International Affairs, 2017)
One of the greatest challenges that confront the International Community today is terrorism. In recent times, through the Boko Haram insecurity challenge, Africa seems to have entered the mainstream of global terrorism. From the activities of the Al Qaeda in the Levant and the Islamic Maghreb, to the clearly desperate drive to acquire territory by the ISIS, in the Levant and in diverse parts of Africa as far south as Mali, terrorism seems to have arrived in black Africa. In recent times, terrorism has taken a new and indeed frightening dimension, particularly through the Boko Haram insurgency in Nigeria. The deadly terrorist activities in the North-East region of Nigeria which range from kidnapping and bombing, through various forms of mindless violence and killings, to outright military confrontation with security agencies in a desperate bid to acquire territory in northern Nigeria, have caused the Nigerian armed forces great losses in human and material resources. This is a study of the international dimensions of the Boko-Haram insurgency in Nigeria. The paper highlighted the immediate and the remote causes of the conflagration that attended the bourgeoning politico-religious conflict which now threatens the stability of the entire West African Sub-region. It is a descriptive analytical survey that utilizes archival materials, library research, extant literature, internet sources and particularly content analysis. The paper recommended a convergence of both domestic and international collaboration to tackle and defeat terrorism in Africa, and concluded that within Nigeria itself, the need for accountability and good governance as a lasting panacea for national security is sine qua non.